Development of qPCR assays for bacterial nitrification and denitrification genes in catfish aquaculture ponds - Caitlin E. Older; Matt J. Griffin; Cynthia Ware; Brian D. Ott (Microbiology Spectrum, 2025)
ABSTRACT Nitrogenous waste products are toxic to fish, and their removal is a critical process in aquaculture production. In earthen pond production systems, such as those used in the catfish industry, phytoplankton act as the dominant sink for ammonia; however, bacteria can also play roles in denitrification and nitrification, particularly when excess ammonia exists. As the US catfish industry continues to intensify, the bacterial communities relevant in the removal of nitrogenous waste will become more integral to efficient production and necessitate further research. Here, quantitative PCR (qPCR) assays targeting four genes covering the denitrification and nitrification pathways present in catfish aquaculture ponds were developed. Twenty-four existing primer sets were used to amplify relevant genes in samples obtained from catfish pond water and sediment and then subjected to high-throughput sequencing to identify the sequence variants present in the environment. Five conventional PCR assays yielded sequencing results conducive to qPCR primer design. Quantitative PCR assays were successfully developed for four targets: amoA, nxrB, napA, and nirK. Application of these assays to sediment and water samples collected from ponds with low or high dissolved oxygen, or no fish (control), demonstrated significant differences in the abundance of amoA, nxrB, and nirK genes. Significantly higher abundances of these genes were found in ponds with low and high dissolved oxygen. In water samples, NO3-N exhibited significant positive correlations with the abundance of three genes (nxrB, napA, and nirK) encoding enzymes that either produce or utilize nitrite.IMPORTANCECatfish aquaculture is the largest aquaculture industry in the United States, by both volume and sales. Production is performed in earthen ponds with no water exchange or filtering systems. Environmental organisms play important roles in maintaining water quality, particularly with respect to nitrogenous waste. Phytoplankton are the dominant sink for nitrogenous waste in earthen pond aquaculture; however, as aquaculture becomes more intensified to meet global population demands, the role of bacteria in nitrogenous waste removal may become more pronounced. To facilitate specific characterization of these important communities in catfish aquaculture ponds, quantitative PCR assays were designed to target genes relevant to bacterial nitrification and denitrification.